Integrated Theological Curriculum Successfully Counters Techno-Pragmatism in Global Education - Adang Hambali; Hasan Basri; Nenden Ahadiah Halimah; Nirwati; Afnie Rizky Nurkamaliyah (Jurnal Isema : Islamic Educational Management, 2026)
Islamic education in the global era faces systemic challenges from educational techno-pragmatism, digital disruption, and ethical crises. This study analyzes the role of integrated theological curriculum in contesting these challenges to foster civilized human beings. Utilizing a qualitative library research method with a descriptive-analytical design, this study examines peer-reviewed literature published between 2019 and 2026. The analysis demonstrates that an integrated theological curriculum successfully counters global techno-pragmatism by restructuring educational orientations ontologically, epistemologically, and axiologically. It systematically operationalizes five dimensions of a civilized human being: spiritual, moral, intellectual, socio-civilizational, and cultural-digital. Furthermore, this study formulates concrete managerial implications for Islamic educational institutions, which encompass restructuring integrated curricula, recruiting value-driven educators, implementing reflective pedagogy, deploying authentic character-based assessments, and cultivating a tawhid-based institutional culture. The findings emphasize that bridging technical management with divine orientations is critical to eliminating academic dichotomy. In conclusion, revitalizing theological values systematically is a fundamental necessity for Islamic educational institutions to produce globally competent graduates without compromising their spiritual and moral identity.